Analysis of coat texture characteristics of bread wheat grains obtained from digital images - Avzalov, Dmitry R.; Arif, Mian Abdur Rehman; Komyshev, Evgenii G.; Koval, Vasily S.; Börner, Andreas; Afonnikov, Dmitry A. (Frontiers in Plant Science, 2025)
IntroductionThe coat texture characteristics of grains in an image are informative parameters often used to classify plants into species or varieties. Intraspecific and interspecies diversity of texture parameters indicates a significant contribution of the genetic component to the formation of these traits. However, the structural and molecular properties of the grain shell, which can determine the texture in the image, have been poorly studied.MethodsHere, a comprehensive analysis of the texture characteristics of bread wheat grains from the International Triticeae Mapping Initiative (ITMI) population was performed based on their digital images.ResultsThe assessment of their diversity revealed two characteristic types of variability: smoothness/roughness and wrinkling along and across the grain axis. It was shown that both genotype and storage duration in the genbank contribute significantly to the formation of all grain texture characteristics investigated. Storage duration was found to be associated with an increase in grain surface roughness. A significant relationship between texture and grain germination was found for only one characteristic, GLCM (gray-level co-occurrence matrix) correlation. QTL analysis identified thirty-six additive and eight pairs of epistatic loci associated with texture traits. These loci were located on eight wheat chromosomes. Prioritization of genes in the identified loci and their functional analysis allowed us to hypothesize a possible link between grain shell texture and cell wall properties.ConclusionThe results demonstrate the genetic and environmental determinants of grain texture traits.